Spatial-temporal abundance and diversity of larval fish in different water bodies (Estuary and Adjacent Coastal Waters) from Sungai Terengganu, Terengganu, Malaysia - Jing, Kai Ooi; Hsieh, Hung-Yen; Li, Lian Wong; Ying, Giat Seah (Penerbit Universiti Kebangsaan Malaysia, 2023)
During larval form, various factors will affect the distributions of fish which lead to spatio-temporal variation of their assemblage. Studies on the variation provide knowledge in understanding the fish ecology. Present study aims to survey the fish larval occurrence in the estuary of Sungai Terengganu and its adjacent waters. A total of 402 larvae samples were collected using a 100 μm mesh sized Bongo net. About 334 samples were identified belonging to 23 families while the rest (equivalent to 16.92% of total catch) were unidentifiable. Three most abundant recorded families are Gobiidae (19.65% of total catch, 2.22 indv. 100 m-3), Ambassidae (12.94% of total catch, 1.47 indv. 100 m-3) and Apogonidae (9.45% of total catch, 1.02 indv. 100 m-3). Based on cluster analysis, fish larvae were divided into two groups whereby one from estuary of Sungai Terengganu and another one from its adjacent coastal water with little overlapping between them. Estuary observed higher larval density than adjacent coastal waters while larval taxa diversity recorded to be higher in the adjacent coastal waters compared to the estuary. Throughout sampling months, two larval mean density peaks were observed during June 2019 (76.19 indv. 100 m-3) and January 2020 (105.38 indv. 100 m-3).